Disability Theatre as Critical Participatory Action Research: Lessons for Inclusive Research - Rachelle D. Hole; Leyton Schnellert (Social Sciences, 2024)
Informed by critical disability studies and disability justice, this article describes the reflections of two university researchers co-researching with self-advocates (individuals with intellectual disability), theatre artists, researchers, and a community living society to create social justice disability theatre as critical participatory research (CPAR), demonstrating how disability theatre can contribute to and advance inclusive research practice. Disability justice-informed theatre as CPAR has direct relevance to people with intellectual disabilities; offers a platform where self-advocates’ diverse ways to communicate and be in the world are honoured and taken up as resources to the research and community; and can generate mentorship opportunities for self-advocates to learn, practice, and develop research skills. Significances include showing how the theatre creation process (devising, developing, and refining scenes) is research in itself and how tensions are recognized as sites of possibility. Future research should explore how increasing pathways to communication, co-creation of KT strategies, and protocols for power sharing and problem solving within disability theatre as CPAR impact the roles, outcomes, and experiences of disabled and non-disabled researchers and audience members.